The United States and Portuguese Decolonization - Rodrigues, L. N. (Portuguese Studies, 2013)
This article argues that US policy regarding Portuguese colonialism and decolonization followed the general patterns of US African policy during the Cold War. The narrative of US-Portuguese relations demonstrates that, despite the growing interest in African affairs since the late 1950s, Europe continued to be the political centre of the Cold War throughout the decades. The fear of losing the strategically located Azores base in a period of several important Cold War episodes, such as the Berlin and Cuban crises, and the Vietnam and Yom Kippur wars, outweighed the concerns with African developments and the rhetoric of anti-colonialism that briefly emerged in the late 1950s and the early 1960s.